MIMO Printed Dipole Antenna for Wimax Network Usage Application - S Susanzefi; Irawan Hadi; Ciksadan Ciksadan; Halimah Thussyadiyah (Journal of Telematics and Informatics, 2020)
Standard wimax have 2 versions : IEEE 802.16-2004 and IEEE 802.16d. this comprehension also supported by Orthogonal Frequency Division ultiplexing  on Physical Layer. OFDm provide wireless DSL technology where broadband cable is not available. Wimax 802.16e use Standard OFDMA Technic. It provide the support for nomadic and mobility service also known as WiMAX phone. Wimax is a wireless broadband technology that have an improvement on WI - FI and UMTS. One of the devices that is needed in the technology is the antenna. The technique used is the MIMO technique. MIMO technique uses multiantene or more than one antenna from both the transmitter and receiver sides. The design and realization of the antenna in this paper is used for 5G devices in the future that work at a frequency of 5.4 GHz - 5.6 GHz. Antenna simulation shows that the planned working frequency is between 5.4 GHz to 5.6 GHz, has a Return Loss of -20.007 dB, VSWR ≤ 2, which is 1.2216, 414 MHz bandwidth, gain of 3.898 dB, impedance of 50.00 Ohm, Omnidirectional radiation pattern. From the design and analysis, this antenna can be used as a 5G technology antenna for the future.